(untitled) (Acta Entomologica Serbica, 2015)
Although fauna of Serbian Orthoptera was studied in details during 19th and 20th century, a total number of species and their distribution is still insufficiently known. The area of southern Serbia is particularly interesting due to possible presence of species distributed in Mediterranean and sub-Mediteranean, such as Anacridium aegyptium (Linnaeus, 1764) found on a tarred road close to Macedonia. Although it was supposed to inhabit Serbia, no confirmed records have been known. As the specimen was observed out of its habitat, a more detailed study on its distribution and ecology is required. Also more attention should be given to fauna of Orthoptera of southern Serbia.